Ag/polydopamine-modified Ti/TiO2 nanotube arrays: A platform for enhanced CO2 photoelectroreduction to methanol - Perini, João Angelo Lima [UNESP]; Torquato, Lilian D. Moura [UNESP]; Irikura, Kallyni [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2019)
TiO2 nanotube (NT) arrays were modified with thin films of polydopamine (PDA) and Ag nanoparticles (NP) and were used as electron storage centers on a photoelectrode surface, in order to drive the reduction of CO2 to methanol. Silver nanoparticles were obtained by means of chemical deposition using the catechol groups present in PDA. The Ti/TiO2NT@PDA-AgNP photocathode presented higher photocurrents when irradiated using either UV-vis irradiation or a solar simulator, compared to bare Ti/TiO2NT, indicating improvement of charge carrier separation, while the band gap of the material decreased from 3.12 to 2.3 eV. Under optimized conditions, methanol production of 59.5 μM cm-2 was achieved and under the solar simulator, 19.25 μM cm-2 of methanol was generated, indicating that the PDA-AgNP coating improved the activation by visible light. The Ag present in the modified Ti/TiO2NT electrodes was quantified during photoelectrocatalysis, with the amount of Ag nanoparticles released from the electrodes being negligible. A schematic representation of the charge transfer mechanism at the Ti/TiO2NT@PDA-AgNP electrode is provided.
Keywords: CO2 reduction; Dopamine; Photoelectrocatalysis; Silver; Solar simulator